Indonesian-English Code-Mixing in Entertainment-Based Communication on X - Listya Arum Ridhawati; Anggi Rizky Firdhani; Muhammad Nur Assyddyq (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to investigate the patterns of Indonesian-English code-mixing in entertainment-focused communication on X. The study is grounded in Muysken’s (2000) typology of code-mixing, which classifies linguistic blending into insertion, alternation, and congruent lexicalization. The data were sourced from 157 posts collected from seven selected entertainment accounts on X from May 1 to June 30, 2025. Entertainment accounts were chosen because they often employ multilingual expression to attract and engage diverse audiences. Employing a qualitative research design, data were gathered using the documentation technique, which involved selecting posts containing Indonesian-English code-mixing. The analysis applied Muysken’s framework to categorize each instance into one of the three types. The results reveal that insertion was the most frequent type (78.34%), followed by congruent lexicalization (12.10%) and alternation (9.55%). These findings confirm the consistent dominance of insertion across various online and social media contexts, while also showing that the leading type can vary depending on discourse domains. The research strengthens the relevance of Muysken’s framework in digital sociolinguistics, providing insights for content creators and digital marketers in engaging multilingual audiences effectively.